THE ROLE OF RELIGIOSITY AS MODERATION IN THE EFFECT OF BRAND IMAGE ON REPURCHASE INTENTION AMONG MCDONALD’S CONSUMERS IN BANDUNG CITY - Ichsan Wicaksono; Edi Nurjahjadi (Journal of Management Small and Medium Enterprises (SME's))
This research examines how brand image influences repurchase intention among McDonald's customers in Bandung City, with religiosity serving as a potential moderating factor. The study employed quantitative methodology, surveying 200 purposively selected participants aged 17-45. The findings indicate that brand image has a negative effect on repurchase intention, while religiosity does not significantly moderate this relationship. Despite a strong brand image, repurchase intention remains low due to contextual sensitivities. These results highlight the importance of integrating religiosity-related considerations into marketing strategies during global geopolitical tensions.